TINGKAT KETERAMPILAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL LUAS PERMUKAAN BANGUN RUANG SISI DATAR - Sembadra, Adhelways Ria; Sunardi, Sunardi; Trapsilasiswi, Dinawati (Department of Mathematics Education , University of Jember, 2017)
Abstract. The research proposed to describe about student creative thinking skill in resolving about the flat sides shape surface area in class VIII D SMPN 2 Jember about 31 students.An instruments used is creative thinking skills package test, interview guidelines, and tests validation sheets and interview guidelines validation sheets. This research used the creative thinking to identify the capacity to think creative experienced students.This research used three aspects creative thinking that includes fluency, flexibility and organility. In this research known the percentage the aspects creative thinking students namely 40,59 % on the aspect of fluency, 33,33 % on the aspect of flexibility and 26,07 % on the aspect of originality. According to the research, average of class VIII D SMPN 2 Jember most students are on TBK 1 ( less creative ) with percentage 29,03 %, then category students have creative with the percentage 25,81 %, creative 25,81 % and the lowest is the number of students categories creative enough with the percentage 19,35 % Keywords: Originallity, Fluently, Fleksibility, Creative Thinking Level